Analisa Nilai Perusahaan Pada Perusahaan Sektor Industri Barang Konsumsi - Maria Stefani Osesoga; Michelle Vanessa (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
The purpose of this research is to obtain empirical evidence about the effect of profitability (ROA), liquidity (CR), firm growth, and capital structure (DER), towards firm value (PBV). Firm value is very important because it reflects on the company’s performance that can affect on investor’s perception towards the company. The sample in this study was selected using the purposive sampling method and secondary data were analyzed using multiple linear regression models. The results of this research are profitability, liquidity, and capital structure have a positive significant effect on firm value. Meanwhile company growth has a negative significant effect on firm value.